Response of elephant peripheral blood mononuclear cells when stimulated with elephant endotheliotropic herpesvirus glycoprotein B (EEHV-gB) - Sittisak, Tidaratt; Guntawang, Thunyamas; Srivorakul, Saralee; Photichai, Kornravee; Boonprasert, Khajohnpat; Khammesri, Siripat; Chuammitri, Phongsakorn; Thitaram, Chatchote; Hsu, Wei-Li; Thanawongnuwech, Roongroje; Pringproa, Kidsadagon (Veterinary immunology and immunopathology, 2023)
Elephant endotheliotropic herpesvirus-hemorrhagic disease (EEHV-HD) is the most highly fatal infectious disease among young Asian elephants. Despite the fact that antiviral therapy has been widely used, its therapeutic outcomes remain uncertain. Additionally, the virus has yet to be successfully cultivated in vitro in the process of develop viral envelope glycoproteins for vaccine design. The present study aims to investigate and evaluate EEHV1A glycoprotein B (gB) antigenic epitopes as potential candidates for further vaccine development. Epitopes of EEHV1A-gB were employed in in silico predictions and designed by using online antigenic predicting tools. Candidate genes were then constructed, transformed and expressed in the E. coli vectors prior to examine their potential for acceleration elephant immune responses in vitro. Elephant peripheral blood mononuclear cells (PBMCs) isolated from 16 healthy juvenile Asian elephants were investigated for their proliferative capability and cytokine responses after being stimulated with EEHV1A-gB epitopes. Exposure of elephant PBMCs to 20 µg/mL of gB for 72 h resulted in a significant proliferation of CD3 + cells when compared with the control group. Furthermore, proliferation of CD3 + cells was associated with a marked up-regulation of cytokine mRNA expression, involving IL-1β, IL-8, IL-12 and IFN-γ. It remains to be determined whether these candidate EEHV1A-gB epitopes could activate immune responses in animal models or elephants in vivo. Our potentially promising results demonstrate a degree of feasibility for the use of these gB epitopes in expanding EEHV vaccine development. •EEHV glycoprotein B (gB) is essential as target for EEHV vaccine development.•EEHV1A-gB antigenic ectodomain at amino acid residues of 541–635 significantly stimulated the proliferation of elephant T lymphocytes in vitro.•The EEHV1A-gB antigenic epitope residues 541–635 may be used as an alternative antigenic epitope in the design of EEHV vaccines.